2021
DOI: 10.1063/5.0052182
|View full text |Cite
|
Sign up to set email alerts
|

In situ water radiolysis in a scanning electron microscope and observation of micro- and nanobubbles formation

Abstract: Nanobubble formation by radiolysis of water has been observed in a transmission electron microscope using very high electron dose ratios. Here, surface micro- and nanobubbles were formed in situ in a conventional scanning electron microscope at relatively low magnifications of ∼1000. Bubble formation was observed at a low dose ratio of 1.3 × 1011 electrons/cm2 s, which is 5–7 orders of magnitude smaller than in previous studies using transmission electron microscopes. Our observations suggest that the pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For example, Tan et al [50] concluded that bulk nano-bubbles stabilise at a typical radius of ∼100 nm and that this radius increases with ionic concentration. Furthermore, Takahara and Suzuki [55] demonstrated that nano-bubbles survive even for days under certain conditions.…”
Section: Unresolved Gaseous Structuresmentioning
confidence: 99%
“…For example, Tan et al [50] concluded that bulk nano-bubbles stabilise at a typical radius of ∼100 nm and that this radius increases with ionic concentration. Furthermore, Takahara and Suzuki [55] demonstrated that nano-bubbles survive even for days under certain conditions.…”
Section: Unresolved Gaseous Structuresmentioning
confidence: 99%